2003
DOI: 10.1046/j.1365-2796.2003.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture versus placebo versus sumatriptan for early treatment of migraine attacks: a randomized controlled trial

Abstract: Objectives. To investigate whether acupuncture is superior to placebo and equivalent to sumatriptan for the early treatment of an acute migraine attack. Design. Randomized, partly double-blind (sumatriptan versus placebo) trial. Setting. Two hospitals in Germany (one specialized in traditional Chinese medicine and one in the treatment of headache). Subjects. A total of 179 migraineurs experiencing the first symptoms of a developing migraine attack. Interventions. Traditional Chinese acupuncture, sumatriptan (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 24 publications
4
37
0
4
Order By: Relevance
“…Effects found in this study that have been previously reported include: differences between acupuncture and control for migraine 7,12,45 that increased between posttreatment and 1-year follow-up, 11 unconvincing effects for tension-type headache, [46][47][48][49] improvements in severity and frequency, 24 and increased benefit in patients with greater headache severity.…”
Section: Comparison With Other Studiessupporting
confidence: 64%
See 2 more Smart Citations
“…Effects found in this study that have been previously reported include: differences between acupuncture and control for migraine 7,12,45 that increased between posttreatment and 1-year follow-up, 11 unconvincing effects for tension-type headache, [46][47][48][49] improvements in severity and frequency, 24 and increased benefit in patients with greater headache severity.…”
Section: Comparison With Other Studiessupporting
confidence: 64%
“…Nonetheless, good evidence from randomised trials shows that acupuncture is superior to placebo in the treatment of migraine. 7,12 Furthermore, this study was modelled on Vincent's earlier double-blind, placebocontrolled trial in migraine, 11 which makes direct comparison possible. Raw data were obtained from the author and results compared directly between trials.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another problem with sham acupuncture is that sham acupuncture modalities can be distinguished from true acupuncture by experienced patients. 28 Thus it is essential that there is little difference in protocol between the control intervention and true treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A local twitch response (LTR) to snapping palpation, pressure, or needle activation of a trigger point is a characteristic finding in this syndrome [44]. The muscle bands affected are palpably taught, with a focal-sensitive area referred to as a trigger point.…”
Section: Discussionmentioning
confidence: 99%